Impact of an integrated whiteboard system on physics QA turnaround time. Issue 7 (19th June 2022) - Gates, Evan; Chiang, Bing‐Hao; Kalet, Alan; Kim, Minsun
Abstract: Purpose: To evaluate the impact of a digital whiteboard system integrated with data from the oncology information system (OIS) on the urgency of physics quality assurance (QA) tasks in the radiation oncology department. Methods: Quality check list (QCL) items in the Mosaiq OIS corresponding to eight discrete, sequential steps in the treatment planning process were created. A whiteboard to graphically display active QCLs automatically and in real time was implemented in March 2020 using R shiny. QCL data with completion status were collected in two 12‐month time periods before and after whiteboard implementation: January 2019–December 2019 and July 2020–June 2021. For all plans requiring patient‐specific QA, we recorded when each plan was available for physics QA and which treatments started the following day. We further classified those plans into four categories (urgency levels 1–4 with 4 being the most urgent) depending on how much time was available to perform QA. We compared the proportion of these next‐day QAs in each category between time periods accounting for plan type, day of the week, and time of year. Results: Overall QA numbers were similar between time periods with 797 and 765 QAs total. The total proportion of next‐day QA decreased by 27% and the proportions of urgency levels 1 and 4 both showed significant decreases after whiteboard implementation of 29.2% and 54.9%, respectively ( p < 0.05 p<0.05 ). All plan types had reduced proportions of next‐day QAs, especially nonstereotactic body radiation therapy (non‐SBRT) (30.3% decrease, p < 0.05 p < 0.05 ). Fridays and the months of October–December had the highest proportion of next‐day QAs but showed significant reductions of 19.1% and 40.6% in the proportion of next‐day QAs, respectively ( p < 0.05 p<0.05 ). Conclusions: The integrated whiteboard system significantly reduced the proportion of last‐minute physics work, increasing patient safety. Advantages of the integrated whiteboard were low cost, low overhead with automatic interface to the OIS, and concurrent user support.